CHARACTERIZATION PHYSICAL AND CHEMICAL OF SESAME SEED OIL (Sesamum indicum L.) METHYL ESTER AND COMPOSITION - NMC, Aji Zaldya; Daniel, Daniel; Hiyahara, Irfan Ashari; Magdaleni, Agustina R (JURNAL KIMIA MULAWARMAN; Vol 20 No 2 (2023), 2023)
The methyl ester of sesame seed oil (Sesame seeds L.) was used to make diethanolamide. This process involvedextraction, transesterification, and amidation. The research revealed that extraction by maceration yielded a sesame seed oil yield of 36.14 percent, an acid number of 1.1531 mg KOH/g, a FFA number of 0.5796 percent, and a saponification number of 51.287 mg KOH/g. In the process of converting sesame seed oil to methyl ester, the acid number was 0.5126 mg KOH/g, the FFA number decreased to 0.2704%, and the saponification number was 50.049 mg KOH/g. According to methyl ester GC-MS analysis, methyl oleate made up 39.13% of the methyl ester of  sesame seed oil. The methyl ester FT-IR spectrum exhibits a specific absorption peak at 1743 cm-1 for C=O ester.